1995
DOI: 10.4049/jimmunol.154.4.1810
|View full text |Cite
|
Sign up to set email alerts
|

Isotype switching from IgG3 to IgG1 converts a nonprotective murine antibody to Cryptococcus neoformans into a protective antibody.

Abstract: Passively administered mAbs to Cryptococcus neoformans capsular polysaccharide can alter the course of infection in mouse models. In preliminary studies of passive Ab efficacy, most IgM, IgA, and IgG1 mAbs were protective, but the few IgG3 mAbs tested did not confer significant protection. Because IgG3 is effective in pneumococcal infections, this phenomenon was examined more rigorously by generating an IgG1 switch variant from the non-protective IgG3 mAb 3E5 and comparing its protective efficacy in a murine m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…In summary, our results 1) demonstrate the presence of two additional GXM epitopes (recognized by group III and IV mAbs) associated with prolongation of survival and enhanced effector cell activity, 2) indicate that differences in affinity affect the ability of mAbs to prolong survival in vivo and mediate the attachment and ingestion phases of phagocytosis by effector cells in vitro, 3) suggest that both extracellular and intracellular mechanisms are involved in mAb-mediated effector cell fungicidal/fungistatic activity, and 4) support the association between mAb protective efficacy and binding to C. neoformans with an annular capsular immunofluorescence pattern. Previous studies have shown that IgG1 anti-GXM mAbs can prolong survival (17,22,27,36,50). This study extends those findings by demonstrating functional differences for IgG1 mAbs that differ in variable gene utilization, epitope specificity, and affinity.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In summary, our results 1) demonstrate the presence of two additional GXM epitopes (recognized by group III and IV mAbs) associated with prolongation of survival and enhanced effector cell activity, 2) indicate that differences in affinity affect the ability of mAbs to prolong survival in vivo and mediate the attachment and ingestion phases of phagocytosis by effector cells in vitro, 3) suggest that both extracellular and intracellular mechanisms are involved in mAb-mediated effector cell fungicidal/fungistatic activity, and 4) support the association between mAb protective efficacy and binding to C. neoformans with an annular capsular immunofluorescence pattern. Previous studies have shown that IgG1 anti-GXM mAbs can prolong survival (17,22,27,36,50). This study extends those findings by demonstrating functional differences for IgG1 mAbs that differ in variable gene utilization, epitope specificity, and affinity.…”
Section: Discussionsupporting
confidence: 83%
“…Passive immunization studies using mAbs generated against the GXM-TT have demonstrated that 1) both protective and nonprotective Abs are elicited in response to this glycoconjugate (22,34); and 2) major determinants of Ab efficacy are isotype (22) and epitope specificity (22,34,35). mAbs of the IgG1 isotype are highly protective (14 -17, 33), whereas mAbs of the IgG3 isotype have been shown to be poorly protective or disease enhancing (22,36). mAbs bind with either a punctate or annular indirect immunofluorescence pattern to the C. neoformans capsule.…”
mentioning
confidence: 99%